The development of rural entrepreneurship in Romania - Fehér Andrea (Review on agriculture and rural development, 2014)
Small and medium enterprises play a vital role within the economy of a country, representing a source of entrepreneurial and innovation skills that greatly contributes to the achievement of gross domestic product and employs a large part of the labor force. The rural economy is more developed and dynamic, as it has a structure more diverse, and the share of non-agricultural economy is higher. The purpose of this article is to perform a radiography on the business environment in Romanian rural areas by identifying the main strategic ways for stimulating entrepreneurial spirit. Rural communities in Romania is mostly characterized by an aging population, declining birth rates and dependence on agriculture, especially the subsistence and semi-subsistence. Sources of income are reduced due to the low number of jobs and have major implications on quality of life in rural communities. Therefore, local authorities should be concerned about the development of their localities and improving the quality of life through the successful implementation of development programs and projects.